Successful treatment of refractory thrombotic thrombocytopenic purpura associated with systemic lupus erythematosus with combination of plasma exchange and low-dose rituximab. (December 2020) - Ma, Wanlu; Bai, Wei; Wu, Xueyan; Zhao, Jiuliang; Li, Mengtao; Zeng, Xiaofeng
Objectives: Thrombotic thrombocytopenia purpura (TTP) associated with systemic lupus erythematous (SLE) (i.e., SLE-TTP) is a rare life-threatening disease often requiring intensive immunosuppressive agents, in addition to high-dose corticosteroids and plasma exchange (PEX). The optimal therapy of rituximab is unclear, but 375 mg/m 2 weekly for 4 weeks is the usual practice, adopted from regimens for non-Hodgkin's lymphoma. We reported two cases of refractory SLE-TTP that showed good efficacy and prognosis with combination of methylprednisolone (MP) pulse, plasma exchange and low-dose rituximab (100 mg weekly for 4 weeks) treatment. Methods: Clinical data and treatment outcomes were reviewed of two patients diagnosed with refractory SLE-TTP at Peking Union Medical College Hospital between July 2017 and July 2018. Results: Both patients had SLE and presented with microangiopathic anemia and thrombocytopenia. Laboratory assays revealed high anti-nuclear antibody titers, reduced complement 3 and 4 levels, proteinuria, significantly elevated lactate dehydrogenase, schistocytes on peripheral blood smear, low ADAMTS13 activity, and the presence of ADAMTS13 inhibitor. In both patients, platelet counts remained below 50 × 10 9 /L after MP pulse and 6 PEXs, confirming the diagnosis of refractory SLE-TTP. Low-dose rituximab (100 mg weekly for 4 weeks) was administered in both cases, resulting in normalization of platelet counts and significant reductions in B-lymphocyte counts. No TTP relapse or SLE flare occurred during 24 months of follow-up. Conclusions: Our cases confirmed the efficacy and good follow-up outcomes of low-dose rituximab treatment (100 mg weekly for 4 weeks) for refractory SLE-TTP.